Species Richness of Bivalves at Aare-Ware and Mirya Rocky Shore of Ratnagiri, Maharashtra, India - Pakhmode, Pallavi Keshav Pakhmode; S.A. Mohite; R. A. Pawar; S. S. Lokhande; A.M. Meshram (Journal of Indian Fisheries Association, 2023)
In the present study data was collected fortnightly intervals from May 2014 to April 2016 from Aare-Ware and Mirya rocky shore of Ratnagiri. Total 12 species of bivalves representing 4 orders, 5 families and 10 genera were recorded from the Aare-Ware and Mirya rocky shore of Ratnagiri. Bivalves belonging to families Ostreidae, Mytilidae and Veneridae were recorded during the study. Species richness of Aare-Ware shore in the year 2014-2015 was high as compared to 2015-2016 while at Mirya shore species richness in the year 2014-2015 was low as compared to 2015-2016.